PENGEMBANGAN EKSKUL JURNALISTIK DI MTs NEGERI 1 KOTA SURABAYA BERBASIS MEDIA SOSIAL - Yuni Listiana; Muhajir Muhajir (Politeknik Negeri Sriwijaya, 2021)
Social media is an online media (in a network), where users can easily participate, share, and create content on blogs, social networks, wikis, forums, and virtual worlds. One of the social media that is currently going global is Instagram. Instagram is a photo and video sharing application that allows users to take photos, take videos, apply digital filters, and share them with various social networking services including Instagram itself. MTsN 1 Kota Surabaya has a journalistic extracurricular that aims to develop potential, interests, talents, and abilities in the field of writing. The journalistic extracurricular of MTsN 1 Kota Surabaya itself does not yet have a social media to make this extracurricular known by the public in the sense that it expands the readership so that it is not only in the school environment but by the wider community. Therefore, in this service, the Teacher Training and Education Faculty (FKIP) carried out community service activities by introducing and creating an Instagram account so that journalistic extracurriculars could be used to write a photo caption of activities at MTsN 1 Surabaya City, as well as edit and post the photo.